2017
DOI: 10.1016/j.jclinepi.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Quality of missing data reporting and handling in palliative care trials demonstrates that further development of the CONSORT statement is required: a systematic review

Abstract: ObjectivesAssess (i) the quality of reporting and handling of missing data (MD) in palliative care trials, (ii) whether there are differences in the reporting of criteria specified by the Consolidated Standards of Reporting Trials (CONSORT) 2010 statement compared with those not specified, and (iii) the association of the reporting of MD with journal impact factor and CONSORT endorsement status.Study Design and SettingSystematic review of palliative care randomized controlled trials. CENTRAL, MEDLINE, and EMBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 43 publications
2
35
1
2
Order By: Relevance
“…Reasons for attrition vary and may be a result of trial design, patient population or the intervention, but patient withdrawal and loss to follow up are the most common causes [ 19 , 20 ]. Loss to follow up can be a passive form of withdrawal, where patients fail to complete follow up without formally ending their trial involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for attrition vary and may be a result of trial design, patient population or the intervention, but patient withdrawal and loss to follow up are the most common causes [ 19 , 20 ]. Loss to follow up can be a passive form of withdrawal, where patients fail to complete follow up without formally ending their trial involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The CONSORT statement expects reporting of the number of participants who were randomly assigned and the number of participants in each arm included in each analysis . Surveys have shown that 95% of trials in major medical journals report some missing outcome data and 94% of palliative care trials report the number of participants not included in the primary outcome analysis . Systematic reviews have lower rates of reporting numbers of participants with missing data—47% of Cochrane reviews and 7% of non‐Cochrane reviews …”
Section: Meta‐analysis With Missing Datamentioning
confidence: 99%
“…However, even for palliative care drug trials of short duration (4 weeks), attrition has been shown to be high, with only 40% of participants achieving the primary end point in a trial of pregabalin for cancerinduced bone pain [5]. A review of 108 RCTs of palliative care interventions found that the reason for missing data was unclassified in 53%, recorded as loss to follow-up or withdrawal with no further details of the underlying reason [18]. Meta-ethnographic review has identified five themes which may influence nonretention in trials:…”
Section: Introductionmentioning
confidence: 99%